MENINGKATKAN KEAHLIAN PERENCANAAN STARTUP USAHA BAGI MAHASISWA PESERTA WIRAUSAHA MANDIRI - Soegoto, Agus Supandi; Lumanauw, Bode; Soeikromo, Deasy; Mokoginta, Jummie S. L.; Satria, Andi Wiratama; Panyalai, Sitti Sarah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Business startup planning has a strategic value, for the realization of independent entrepreneurial activities that will provide benefits, for increasing knowledge and governance of business startups, efficient business management, and increasing the income potential of entrepreneurial activities carried out. The main problem faced by students in managing a business startup is the lack of knowledge of business planning and good business startup governance, so many business startups fail because they do not meet the business eligibility criteria. This activity aims to: 1) improve business management knowledge and skills through business startup planning for students, and 2) improve skills through understanding how to build a startup business, to be able to grow and master niche markets in the environment quickly and profitably. This community service was carried out at the auditorium of Universitas Dumoga Kotamobagu, North Sulawesi province. The methods used are planning simulations and case studies of building a start-up business, discussions, and role play to improve participants' knowledge and skills. The results of the activity were obtained as an illustration of an increase in the ability of participants to make business plans based on good business management principles, increased performance in making alternative business plans and solutions to achieve business targets, increasing the ability to plan a startup business to master the market well, and having reliable profitability to develop their business well. Keywords: Planning, Startup, Management, Operating profit